2011
DOI: 10.3130/jaabe.10.217
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Aluminum Waste for Concrete Production

Abstract: Aluminum wastes (AW) have been used to produce concrete samples used for this work. Tests on the setting times, compressive and flexural strengths were conducted at replacement levels of 5, 10, 20, 30 and 40 % by weight of cement. The results showed that AW can be used as a retarder and thus, a good material for hot weather concreting. Optimum replacement values for the compressive and flexural strengths are at 10 % replacement ant the statistical models developed on them are significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 3 publications
(1 reference statement)
1
22
0
1
Order By: Relevance
“…This process of strength development is expected to continue with hydration period until completion of hydration of cement -Cellulose industrial residue mixture [3]. These results confirm those obtained by other researchers using similar materials [9,20,21]. …”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…This process of strength development is expected to continue with hydration period until completion of hydration of cement -Cellulose industrial residue mixture [3]. These results confirm those obtained by other researchers using similar materials [9,20,21]. …”
Section: Methodssupporting
confidence: 81%
“…Thus, cellulose industrial residue defers the hydration of the paste and extends the setting time. This shows that cellulose industrial residue can be used as a retarder and thus, is a good material for hot weather concreting, like aluminum waste [20]. Table 4 shows the compressive strength of OPC/CIR concrete mixes with different CIR contents and with different hydration period.…”
Section: Methodsmentioning
confidence: 99%
“…Kuat tarik belah beton adalah nilai kuat tarik tidak langsung dari benda uji beton yang berbentuk silinder, yang diperoleh dari pembebanan benda uji tersebut yang diletakkan secara mendatar, sejajar dengan permukaan meja penekan mesin uji tekan [5] . Kuat tarik belah diperoleh dengan metode pengujian kuat tarik belah menggunakan universal testing machine (UTM).…”
Section: Kuat Tarik Belahunclassified
“…AW has also been used as a cement replacement in the manufacturing of conventional concrete. Elinwa [ 31 ] reported that with a 10% cement replacement, the compressive and flexural strength was similar to that of conventional control concrete.…”
Section: Introductionmentioning
confidence: 99%